2002
DOI: 10.1136/bmj.325.7370.934
|View full text |Cite
|
Sign up to set email alerts
|

Managing depression as a chronic disease: a randomised trial of ongoing treatment in primary care

Abstract: Objectives To evaluate the long term effect of ongoing intervention to improve treatment of depression in primary care. Design Randomised controlled trial. Setting Twelve primary care practices across the United States. Participants 211 adults beginning a new treatment episode for major depression; 94% of patients assigned to ongoing intervention participated. Intervention Practices assigned to ongoing intervention encouraged participating patients to engage in active treatment, using practice nurses to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 41 publications
4
123
1
2
Order By: Relevance
“…30 Primary care physicians provide the bulk of care for individuals with depression, diabetes, and other chronic illnesses, 37 and research indicates that enhancing self-efficacy can improve health behaviors and outcomes among chronically ill patients. [19][20][21][22][23][24][25][26][27][28][29] Prior studies also indicate that physicians' behaviors during standardized patient encounters correlate with their behaviors during real patient visits. 38,39 In this context, the combined findings of our practicing PCP- Additional studies are warranted to examine whether the effects we observed will generalize to real patients and will lead to improved health behaviors and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Primary care physicians provide the bulk of care for individuals with depression, diabetes, and other chronic illnesses, 37 and research indicates that enhancing self-efficacy can improve health behaviors and outcomes among chronically ill patients. [19][20][21][22][23][24][25][26][27][28][29] Prior studies also indicate that physicians' behaviors during standardized patient encounters correlate with their behaviors during real patient visits. 38,39 In this context, the combined findings of our practicing PCP- Additional studies are warranted to examine whether the effects we observed will generalize to real patients and will lead to improved health behaviors and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques were drawn from self-efficacy theory, other relevant behavioral theories, direct observation of primary care, and research-proven approaches to enhancing self-efficacy and promoting healthy behaviors. [19][20][21][22][23][24][25][26][27][28][29] Figure 1 Study self-efficacy-enhancing interviewing techniques and their presentation sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A model of care suited to chronic diseases has been effectively used for medical conditions such as hypertension, diabetes, and asthma, and evidence from well-conducted primary care based studies indicates that this approach is effective for depression (Rost et al, 2002;Dietrich et al, 2004). It appears that the principles of this management approach -explicit evidence-based guidelines, patient education for self-management, stepped care involvement of specialist resources, links with community resources -together with the organisational changes required to embed these approaches within services (information systems such as patient registers, reminders, progress indicators; and new staff roles and ways of working such as primary care nurse case managers, and tele-support) are a central part of effective interventions strategies (Von Korff & Goldberg, 2001).…”
Section: Common Mental Disorder -Potential For Chronicitymentioning
confidence: 99%
“…One approach to improve mental health care in primary care settings is the "collaborative care" model [4][5][6][7], closely patterned on the "chronic disease model" [8]. Various forms of the collaborative care model have been tested but some features are common to all.…”
Section: Introductionmentioning
confidence: 99%